The impact of the Commonwealth on Churchill's Europe (Comillas Journal of International Relations, 2016)
Focusing from the time of his electoral defeat in July 1945 until the end of his second term as Prime Minister (October 1951-April 1955), this article examines the impact the Commonwealth had on Churchill’s Europe. Following the end of the Second World War Churchill’s Europe was fragile, yet not broken beyond all repair. Rather than weaken world organisations, such as the United Nations or a united post-war Europe, Churchill argued that the British Commonwealth would strengthen such liaisons. Analysing Churchill’s key relationships with the heads of the Commonwealth, reveal him to have been a true European – where security and democracy took precedence. His realism and pragmatism in the face of ever-changing, everevolving world-wide post-war alliances, where the Commonwealth arguably played a significant role, offers a stark contrast to the more common image of Churchill the “die-hard” imperialist.
Keywords: Churchill; Commonwealth; India; Nehru; Australia; Menzies; Curtin; South Africa; Smuts; New Zealand; Fraser; Holland; ANZUS; America; Canada; St. Laurent; Cold War; Korean War; Malayan Emergency.